Source apportionment of air pollution: a case study in Malaysia - Azid, Azman; Juahir, Hafizan; Toriman, Mohd Ekhwan; Enduta , Azizah; Kamarudin, Mohd Khairul Amri; Abdul Rahman, Mohd Nordin; Che Hasnam, Che Noraini; Mohd Saudi, Ahmad Shakir; Yunus, Kamaruzzaman (Universiti Teknologi Malaysia, 2015)
Air pollution is becoming a major environmental issue in Malaysia. This study focused on the identification of potential sources of variations in air quality around the study area based on the data obtained from the Malaysian Department of Environment (DOE). Eight air quality parameters in ten monitoring stations for seven years (2006 – 2012) were gathered. The Principal Component Analysis (PCA) method from chemometric technique was applied to identify the source identification of pollution around the study area. The PCA method has identified methane (CH4), non-methane hydrocarbon (NmHC), total hydrocarbon (THC), ozone (O3) and particulate matter under 10 microns (PM10) are the most significant parameters around the study area. From the study, it can be concluded that the application of the PCA method in chemometric techniques can be applied for the source apportionment purpose. Hence, this study indicated that for the future and effective management of the Malaysian air quality, an effort should be placed as a priority in controlling point and non-point pollution sources.